Experimental Demonstration of RGB LED-Based Optical Camera Communications - Pengfei Luo; Min Zhang; Zabih Ghassemlooy; Hoa Le Minh; Hsin-Mu Tsai; Xuan Tang; Lih Chieh Png; Dahai Han (IEEE Photonics Journal, 2015)
Red, green, and blue (RGB) light-emitting diodes (LEDs) are widely used in everyday illumination, particularly where color-changing lighting is required. On the other hand, digital cameras with color filter arrays over image sensors have been also extensively integrated in smart devices. Therefore, optical camera communications (OCC) using RGB LEDs and color cameras is a promising candidate for cost-effective parallel visible light communications (VLC). In this paper, a single RGB LED-based OCC system utilizing a combination of undersampled phase-shift on–off keying (UPSOOK), wavelength-division multiplexing (WDM), and multiple-input–multiple-output (MIMO) techniques is designed, which offers higher space efficiency (3 bits/Hz/LED), long-distance, and nonflickering VLC data transmission. A proof-of-concept test bed is developed to assess the bit-error-rate performance of the proposed OCC system. The experimental results show that the proposed system using a single commercially available RGB LED and a standard 50-frame/s camera is able to achieve a data rate of 150 bits/s over a range of up to 60 m.